Synthesis and characterization of branched polymers - Aboelanin, Hamza Mahmoud Ahmed Mahmoud (Univerzita Pardubice, 2023)
The dissertation deals with the separation and characterization of the molar mass and molar mass distribution and molecular structure in details of different types of branched polymers (methacrylate branched polymers and polyolefins). The molar mass and molar mass distributions, and branching studies for all the prepared methacrylate?s branched polymers were determined by size exclusion chromatography with a multi-angle light scattering detector DAWN NEON, an RI detector Optilab NEON and an online viscometer ViscoStar NEON. While the separation and monitoring methyl (CH3?) and methylene (?CH2?) groups of series of ethylene/1-alkene and ethylene-propylene-diene copolymers (polyolefins) by high temperature-size exclusion chromatography with a filter-based infrared detector (IR5).
Syntéza a charakterizace větvených polymerů
Keywords: Gelová permeační chromatografie (rozměrově vylučovací chromatografie); víceúhlový rozptyl světla; specifický inkrement indexu lomu; větvené polymery; polyolefiny; vnitřní viskozita; větvící poměr; distribuce chemického složení; infračervený detektor; Size Exclusion Chromatography; Multi-angle Light Scattering; Specific refractive index increment; Branched polymers; Polyolefins; Intrinsic viscosity; Branching ratio; Chemical composition distribution; Filter-based infrared detector (IR5)